2012
DOI: 10.1007/s00508-012-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity of the hypothalamic-pituitary-adrenal axis in patients with type 2 diabetes and relations with insulin resistance and chronic complications

Abstract: In type 2 diabetic patients, the HPA axis is clearly hyperactive as evident in increased urinary free cortisol, diminished cortisol suppression after dexamethasone and increased ACTH-induced cortisol levels. Abdominal obesity and the presence of chronic complications increased the HPA axis hyperactivity in type 2 diabetes. Augmentation of positive feedback is associated with insulin resistance and negative feedback with abdominal obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
1
20
0
10
Order By: Relevance
“…Similar meta-analysis concerning 24-h urinary free cortisol (eight studies, [27, 34, 40, 43, 44, 46, 48, 50]) demonstrated a similar lack of overall effect (Fig 3). ES = 2.87 95% CI (-3.63, 9.37), p = 0.387.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Similar meta-analysis concerning 24-h urinary free cortisol (eight studies, [27, 34, 40, 43, 44, 46, 48, 50]) demonstrated a similar lack of overall effect (Fig 3). ES = 2.87 95% CI (-3.63, 9.37), p = 0.387.…”
Section: Resultssupporting
confidence: 54%
“…Two of them found some association between obesity and morning blood cortisol or urinary free cortisol [44, 46]. One study reported morning blood cortisol data of male participants without analyzing potential correlation [45], and the remaining ten clinical observations pooled data of male and female volunteers [27, 2932, 36, 40, 42, 43, 48]. These statistics suggest that an association between peripheral cortisol output and BMI would be more probably found in studies focusing on women.…”
Section: Discussionmentioning
confidence: 99%
“…DM2 patients have elevated basal ACTH levels (Vermes et al 1985, Chiodini et al 2006) and high cortisol levels, both basal and after Dex suppression (Hudson et al 1984, Prpić-Križevac et al 2012. In this regard, the activity of the HPA axis is enhanced in diabetic patients with asymptomatic autonomic imbalance due to prevalent parasympathetic failure.…”
Section: Hpa In Diabetesmentioning
confidence: 99%
“…To date, the pharmacologic mechanism potentially related to the metabolic changes remains unknown. Because hyperactivity of the glucocorticoid system is associated with obesity and insulin resistance (Prpi c-Kri zevac et al, 2012), it is a compelling target for intervention. In preclinical studies, estra-4,9-dien-3-one, 11-[4-(dimethylamino)phenyl]-17-hydroxy-17-(1-propynyl)-(11b,17b)-(9CI), a GR antagonist (GRA) and progesterone receptor antagonist (PRA) medication (Ulmann et al, 1990), reduced the weight gain seen in young obese fa/fa Zucker rats (Langley and York, 1990) and decreased the elevated insulin levels and weight gain observed in olanzapine-treated rats (Beebe et al, 2006).…”
Section: Introductionmentioning
confidence: 99%